Characterization and diversity analysis of hyacinth bean collections in Bangladesh (Bangladesh Journal of Agricultural Research, 2026)
The experiment was conducted with 150 accessions of Hyacinth bean (Lablab purpureus L. Sweet) of which 104 were from Bangladesh and 46 accessions from 17 countries of Asia, Africa and Europe for characterization and diversity analysis. Low to high Shannon-Weaver Diversity Index (0.14 to 0.99) were observed among the 16 qualitative characters. The genotypic and phenotypic coefficient of variations of 19 quantitative characters ranged from 3.59 to 4.08 % and 5.30 to 43.87%, respectively. The accessions were grouped into ten clusters ranging from 8 to 25 accessions. Accessions collected from the same districts in Bangladesh or countries were distributed into different clusters. The results obtained by D2 analysis were also confirmed by canonical analysis. Crosses between accessions belonging to maximum divergent clusters of CPI 106548 (India), ILRI 14437 (Zimbabwe) and TOT 7905 (Uzbekistan) from cluster IX with accessions of BD 122 (Hobiganj, Bangladesh) and BD 8785 (Feni, Bangladesh) from cluster I, and BD 8770 (Gazipur, Bangladesh) from cluster VI for obtaining better variability to the subsequent generation. The breeder can use the selected accessions for varietal improvement of hyacinth bean.Bangladesh J. Agril. Res. 48(1): 01-18, March 2023